Geoelectric Monitoring of Earthen Hydraulic Structure State by Resistivity and Induced Polarization Methods: Mine Water Settling Pond Dam Case Study - Fedorova Olga; Gorshkov Vitaliy (Russian Journal of Earth Sciences)
In earth dams, a permanent filtration of water leads to washing out of sand-clay fraction and to a formation of soil decompression sites, which pose a danger to embankment integrity. Condition monitoring of earth hydraulic structures can be executed by geophysical methods. The article presents the results of geoelectric monitoring conducted on the dam of settling pond of mine water with high metal content. The investigations were carried out by vertical electrical soundings, including electrotomography, and by methods of induced polarization in time and frequency domains. According to the results of the electrical soundings, places of reduced soil resistivity in the dam were identified, associated with infiltration of precipitations and of water from the pond. Geoelectric monitoring showed changes of the soils resistivity in different years, depending on hydrological conditions. Induced polarization methods are sensitive to material composition of soils, such as clayiness and presence of electronically conductive minerals. It is determined that the highest content of clay is in the upper and middle parts of the embankment. In eastern part of the dam, intensive polarizability of the medium was detected. It can be caused by filtration of water, contaminated with metals, through the embankment and sedimentary rocks. Thus, by resistivity measurements, it is possible to identify areas of intensive filtration in the dam body, and induced polarization measurements make it possible to determine clay content in the soil and possible pathways of contamination through the dam, which is of great importance for studying the environmental situation of region.